'I'll Get You, Tom and Jerry. And That Little Dog, Too!': Adaptation, Transmedia, and Franchise Management in the Tom and Jerry and Wizard of Oz Crossovers. (16th August 2021) - McGowan, David
Abstract: This article will offer a close reading of two Warner Bros. direct-to-video animated features— Tom and Jerry & the Wizard of Oz (2011) and Tom and Jerry: Back to Oz (2016)—as an example of the transmedia tendencies of studios in the conglomerate era. Although The Wizard of Oz (1939) and Tom and Jerry were originally MGM productions, the modern distribution of these works provides an insight into the complicated post-'Golden Age' trajectories of studio archives. Ted Turner's brief takeover of MGM in the mid-1980s stripped the studio of many of its assets, while the merger of Turner's company with Warner Bros. in 1996 brought these MGM properties under Warner control. The Tom and Jerry / Wizard of Oz crossover films heavily reference the 1939 MGM movie (the songs, the ruby slippers, and so on)—something that other adaptations of Baum's novels have not been permitted to do. This paper will suggest that these new extensions of old brands subtly rewrite MGM's industrial history in favour of establishing them as Warner Bros. franchises, while also re-establishing the brand identity of the 1939 film at a time where Oz adaptations are facing greater competition, particularly from the successful stage musical Wicked (2003).